Biological corrosion and vegetation in the aspect of permanent ruin - Trochonowicz, Maciej; Klimek, Beata; Lisiecki, Daniel (Protection of Cultural Heritage, 2018)
The article presents the mechanisms of biodegradation of structures in permanent ruins. There are also principles of proceeding in removing undesirable vegetation in these objects. Particular attention was paid to issues related to the diversity of damage caused by biological organisms. Rules for the removal of lichens, algae and fungi algae as well as the procedures for removing unwanted higher plants are presented.